Th17-Inducing Cytokines IL-6 and IL-23 Are Crucial for Granuloma Formation during Experimental Paracoccidioidomycosis - Tristão, Fabrine Sales Massafera; Rocha, Fernanda Agostini; Carlos, Daniela; Ketelut-Carneiro, Natália; Souza, Camila Oliveira Silva; Milanezi, Cristiane Maria; Silva, João Santana (Frontiers in Immunology, 2017)
Paracoccidioidomycosis (PCM), a chronic granulomatous disease caused by the thermally dimorphic fungus Paracoccidioides brasiliensis and P. lutzii, has the highest mortality rate among systemic mycosis. The T helper 1 (Th1)-mediated immunity is primarily responsible for acquired resistance during P. brasiliensis-infection, while susceptibility is associated with Th2-occurrence. Th17 is a population of T CD4+ cells that, among several chemokines and cytokines, produce IL-17A, and requires the presence of IL-1, IL-6 and TGF-β for differentiation in mice, and IL-23 for its maintenance. Th17 have been described as an arm of the immune system that enhances host protection against several bacterial and fungal infections, as Pneumocystis carinii and Candida albicans. In this study, we aimed to evaluate the Th17 immune response and the role of Th17-associated cytokines (IL-6, IL-23 and IL-17A) during experimental PCM. First, we observed that P. brasiliensis infection (Pb18, virulent strain) increased the IL-17A production in vitro and all the evaluated Th17-associated cytokines in the lung tissue from C57BL/6 wild-type (WT) mice. In addition, the deficiency of IL-6, IL-23 or IL-17 receptor A (IL-17RA) impaired the compact granuloma formation and conferred susceptibility during infection, associated with reduced TNF-α, IFN-γ and iNOS expression. Our data suggest that IL-6-production by bone marrow-derived macrophages (BMDMs) is important to promote the Th17 differentiation during Pb18 infection. In accordance, the adoptive transfer of BMDMs from C57BL/6 to infected IL-6-/- or IL-17RA-/- mice reduced the fungal burden in the lungs compared to non-transferred mice and reestablished the pulmonary granuloma formation. Taken together, these results suggest that Th17-associated cytokines are involved in the modulation of immune response and granuloma formation during experimental PCM.